Two novel flavi-like viruses shed light on the plant-infecting koshoviruses - Debat, Humberto Julio; Bejerman, Nicolas Esteban (Springer, 2023)
The family Flaviviridae is composed of viruses with a positive-sense single-stranded RNA genome and includes viruses that are important veterinary and human pathogens. Most members of the family are arthropod- and vertebrate-infecting viruses, but more recently, divergent flavi-like viruses have been identified in marine invertebrate and vertebrate hosts. The striking discovery of gentian Kobu-sho-associated virus (GKaV), along with a recent report of a related virus from carrot, has expanded the known host range of flavi-like viruses to plants, suggesting they could be grouped in a proposed genus tentatively named “Koshovirus”. Here, we report the identification and characterization of two novel RNA viruses that show a genetic and evolutionary relationship to the previously identified “koshoviruses”. Their genome sequences were obtained from transcriptomic datasets of the flowering plants Coptis teeta and Sonchus asper. These two new viruses, which we have named "coptis flavi-like virus 1" (CopFLV1) and "sonchus flavi-like virus 1" (SonFLV1), are members of novel species characterized by the longest monopartite RNA genome observed so far among plant-associated RNA viruses, which is ca. 24 kb in size. Structural and functional annotations of the polyproteins of all koshoviruses resulted in the detection not only of the expected helicase and RNA-dependent RNA polymerase but also of several additional divergent domains, including AlkB oxygenase, trypsin-like serine protease, methyltransferase, and envelope E1 flavi-like domains. Phylogenetic analysis showed that CopFLV1, SonFLV1, GKaV, and the carrot flavi-like virus were grouped together in a monophyletic clade, strongly supporting the recent proposal for creation of the genus “Koshovirus” for the group of related plant-infecting flavi-like viruses.